Electrophysical properties of SmxPb₁₋xTe solid solutions - Hasanov, H.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The electrophysical properties of SmxPb₁₋xTe (x ≤ 0.08) solid solutions have
been investigated. The electric conductivity, Hall coefficient and Hall mobility of charge
carriers in the temperature range 80 to 800 К have been measured. The mechanism of
charge carrier scattering in solid solutions has been ascertained. It is established that
increase of samarium content and simultaneous participation of interacting Sm²⁺ and
Sm³⁺ ions in the transfer process lead to decrease in electric conductivity. The change of
conductivity type from p- to n-type means that obtained solid solutions are partly
compensated semiconductors.